Assessing Healthcare Service Quality with HEALTHQUAL Method and IPA (Case Study: Hasanah Clinic Samarinda) - Ramadhani, Sodik; Pawitra, Theresia Amelia; Widada, Dharma (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Hasanah Clinic Samarinda (KHS) is one of the clinics that provides health services, especially in labor, ultrasound, and MCH services. The purpose of this study was to determine the size of service quality based on the value of the performance level and the level of importance of the HEALTHQUAL attributes, and provide suggestions for improvement based on the priority of IPA diagram improvements at the KHS. The method used to determine the size of service quality is HEALTHQUAL with dimensions of empathy, tangible, safety, efficiency, and improvement. IPA diagrams are used to determine attributes that are prioritized for service quality improvement. From the results of this study, based on measurements with the HEALTHQUAL method at the level of importance obtained that all attributes fall into the category of very important with an average of 4.460. The overall performance level attributes are categorized into the good category with an average of 4.030. Based on the IPA diagram, it is known that five attributes are included in quadrant one which is a priority for improving the service quality. Some suggestions for improvement include making brochures about explanations that are less conveyed, increasing the ability of each midwife, providing financial assistance to medical staff who are deemed necessary to attend training, improving the quality of medical equipment, etc. With this research, it will have a good impact on the health services provided by KHS, because with this research KHS can find out what service attributes are lacking, so that KHS can seek improvements to these service attributes based on the assessment of the level of performance and level of importance.